Study of planter grasp in neonates with hypoxic ischemic encephalopathy - Dr Kamal Kishor Sagaraia; Dr Saurabh Kumar Patel; Dr. S.K. Rao; Dr. Jyoti Singh; Dr H P Singh (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Assessment of primitive reflexes is one of the earliest, simplest and most frequently used assessment tool for neurological status of newborns. Hypoxic ischemic encephalopathy (HIE) is a common cause of neurological morbidity in neonatal period. Aims and Objective: To Study association of planter grasp and its latency and total duration in neonates with HIE. Material and methods: It is an observational, cross sectional study. 145 new born fulfilling criteria of HIE according to Sarnath and Sarnath classification, admitted in the neonatal intensive care unit of S.S. medical college over a period of one year were included. Planter grasp was elicited from 12 hours after birth to 72 hours of birth. Video recording was done simultaneously, and the investigator analyzed the video-clippings and calculated the various parameters with the help of a stop watch with accuracy of 1/100 of a second. Result: Planter grasp was not elicitable in 16.43% of HIE-I, 55% of HIE-II and 83.33% of HIE-III newborns. The latency of Plantar grasp was found to be 0.696 seconds (sec) for HEI-I, 1.689 sec for HIE-II and 0.994 sec for HIE-III and total duration for completion was 1.385 sec for HIE-I, 3.139 sec for HIE –II and 1.858 sec for HIE-III. Conclusion: Absence of planter grasp can be correlated with the increase in severity of HIE. There is significant difference in latency interval and total duration of planter response in different stages of HIE. Detailed examination of primitive reflexes can add in the diagnosis, prognosis and early intervention of high risk newborn especially in resource limited setting where EEG and other neuroimaging facilities are not readily available.